Ketentuan Wudu Bagi Penderita Salas al-Baul Studi Komparatif Antara Pendapat Mazhab Hanafi dan Mazhab Maliki : Wudu Requirements For People Suffering from Salas al-Baul, A Comparative Study Between the Opinions of the Hanafi and Maliki Schools of Thought (AL-FIKRAH: Jurnal Kajian Islam, 2025)
The issue of wudu for people with salas al-baul (urinary incontinence) is debated in various Islamic schools of thought. However, for people with salas al-baul, this condition is a challenge because urine comes out uncontrollably, causing confusion about how to perform ablution and prayer legally according to Shariah. This study aims to examine the provisions of wudu for people with salas al-baul (urinary incontinence) based on the views of the Hanafi Mazhab and the Maliki Mazhab, and compare the legal approaches used by the two madhhabs. The research method used is library research with a normative and comparative approach. The results show that the Hanafi Mazhab provides convenience for people with salas al-baul by allowing wudu to be performed once for each prayer time, without the need to repeat it even if there is urine discharge during prayer. In contrast, the Maliki school takes a stricter approach, requiring the sufferer to make every effort to prevent the discharge of impurities before making wudu. This comparison provides important insights for the development of contemporary fiqh, particularly in providing practical solutions for salas al-baul sufferers.